HELMHOLTZ COILS FOR MEASURING MAGNETIC MOMENTS - P. N. Dobrodeyev; S. A. Volokhov (Приборы и методы измерений)
The optimal configuration of the double Helmholtz coils for measuring of the magnetic dipole moments was defined. It was determined that measuring coils should have round shape and compensative coils – the square one. Analytically confirmed the feasibility of the proposed configuration of these coils as primary transmitters of magnetic dipole moments.